2021
DOI: 10.1073/pnas.2107968118
|View full text |Cite
|
Sign up to set email alerts
|

Structural basis for isoform-specific inhibition of human CTPS1

Abstract: Cytidine triphosphate synthase 1 (CTPS1) is necessary for an effective immune response, as revealed by severe immunodeficiency in CTPS1-deficient individuals [E. Martin et al.], [Nature] [510], [288–292] ([2014]). CTPS1 expression is up-regulated in activated lymphocytes to expand CTP pools [E. Martin et al.], [Nature] [510], [288–292] ([2014]), satisfying increased demand for nucleic acid and lipid synthesis [L. D. Fairbanks, M. Bofill, K. Ruckemann, H. A. Simmonds], [J. Biol. Chem. ] [270], [29682–29689] ([1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(40 citation statements)
references
References 81 publications
(131 reference statements)
3
21
0
Order By: Relevance
“…Ura8 yielded the highest resolution structures, at 2.8 Å (substrates) and 3.8 Å (products) (Figure 3a, table 1). In the Ura8 structures all ligands were clearly visible and bound as previously described for other CTPS homologs, including an iminophosphate reaction intermediate recently observed in drosophila CTPS, and the presence of two distinct CTP binding sites per monomer recently reported in human and drosophila CTPS (Endrizzi et al, 2004;Goto et al, 2004;Lynch et al, 2021Lynch et al, , 2017Zhou et al, 2021) (Figure 3-figure supplement 1c). Ura7 filaments reached lower resolutions, 7.3 Å (substrates) and 3.7 Å (products), but the overall structures were indistinguishable from Ura8 at these resolutions (Figure 3-figure supplement 2, Table 2).…”
Section: Structures Of Yeast Ctps Filamentssupporting
confidence: 75%
“…Ura8 yielded the highest resolution structures, at 2.8 Å (substrates) and 3.8 Å (products) (Figure 3a, table 1). In the Ura8 structures all ligands were clearly visible and bound as previously described for other CTPS homologs, including an iminophosphate reaction intermediate recently observed in drosophila CTPS, and the presence of two distinct CTP binding sites per monomer recently reported in human and drosophila CTPS (Endrizzi et al, 2004;Goto et al, 2004;Lynch et al, 2021Lynch et al, , 2017Zhou et al, 2021) (Figure 3-figure supplement 1c). Ura7 filaments reached lower resolutions, 7.3 Å (substrates) and 3.7 Å (products), but the overall structures were indistinguishable from Ura8 at these resolutions (Figure 3-figure supplement 2, Table 2).…”
Section: Structures Of Yeast Ctps Filamentssupporting
confidence: 75%
“…However, hCTPS2 is regarded as a housekeeping enzyme, whereas hCTPS1 is specifically required for lymphocyte proliferation, and both can produce cytoophidia ( Martin et al, 2014 ). A low affinity of hCTPS1 to feedback inhibition allows the build-up of high CTP levels needed for high cell proliferation ( Lynch et al, 2021 ). If similar adaptations of enzyme characteristics and protein interactions exist in plants is so far unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, At CTPS3 can force At CTPS1 to form mixed filaments, whereas At CTPS1 inhibits filament formation when interacting with At CTPS4. However, up to now, we do not know whether CTPS filaments in Arabidopsis, if they exist in vivo , are inactive, as in Escherichia coli ( Barry et al, 2014 ), or active as observed for mammals ( Lynch et al, 2021 ). While activation of CTPS activity could help counteract imbalances in (deoxy) nucleotide availability during drought progression, inactive cytoophidia could allow for a fast reestablishment of CTPS activity by depolymerization after the drought is over.…”
Section: Discussionmentioning
confidence: 99%
“…Already in the 1970s and 80s, CTPS was suggested to be an attractive target in anti-cancer therapy due to its observed increase in activity leading to elevated CTP levels in lymphocytic and non-lymphocytic leukemia, liver as well as renal carcinoma, and in a variety of other cancers [ 113 , 114 , 115 ]. With the discovery of increased levels of CTPS1 in lymphoblastic as well as other cancer tissues compared to the unchanged levels of CTPS2 in malignant and healthy tissue, targeting CTPS1 has received renewed interest only recently [ 116 , 117 , 118 , 119 ]. More specifically, proteomics analysis of triple-negative breast cancer (TNBC) patient samples revealed an increased expression of CTPS1 compared to para-tumor tissue, which is accompanied by a decrease in disease-free and overall survival of TNBC patients with high levels of CTPS1.…”
Section: Co-targeting Of Pyrimidine De Novo Synthesis and Salvage Pat...mentioning
confidence: 99%
“…Structural binding analysis of co-crystal structures of the newly developed CTPS1 inhibitors R80 and R80 structural analogs revealed specific binding to CTPS1 and all R80 analogs were potent in enzymatic activity assays on recombinant CTPS1. However, their potential as anti-cancer agents targeting CTPS1 alone or in combination with other standard-of-care pyrimidine synthesis inhibitors must be further evaluated in vitro and in vivo [ 119 ].…”
Section: Co-targeting Of Pyrimidine De Novo Synthesis and Salvage Pat...mentioning
confidence: 99%